LOW BACK PAIN DUE TO LUMBAR SPONDYLOSIS AND DISC HERNIATION: A CASE REPORT - Haryani, Heni (Ensiklopedia of Journal, 2020)
Abstract: Low back pain (LBP) remains one of the most prevalent musculoskeletal complaints worldwide, especially among individuals with physically demanding activities. This case report discusses a 51-year-old woman who presented with five months of low back pain radiating to both legs. The symptoms intensified during prolonged sitting or standing and were relieved in a supine position. Her history of frequent heavy lifting was considered a contributing factor. Clinical findings were unremarkable for neurological deficits. Lumbosacral radiography demonstrated anterior osteophyte formation from L1 to L5 and narrowing of the intervertebral space at L5–S1, suggestive of lumbar spondylosis and suspected herniated nucleus pulposus. The patient received conservative treatment, including NSAIDs, muscle relaxants, and neurotropic agents, alongside physiotherapy and postural education. Early diagnosis and interdisciplinary management of chronic LBP are crucial in reducing the risk of long-term functional impairment.Keywords: Low Back Pain, Lumbar Spondylosis, Herniated Nucleus Pulposus.